Analisa Makro Ekonomi pada Perusahaan Pelayaran di Indonesia - Yuniati, Norromadani; Rachman, Farizi; Purwitasari, Ratri Wahyuning (Jurnal Ilmu Manajemen, 2021)
Each country must pay attention to the money market or capital market to take advantage of internationalization opportunities and trade between countries in the Asian region, especially in the maritime sector.Â The success of the capital market in a country, especially in the maritime industry sector, is influenced by external circumstances such as macroeconomic and internal factors such as its performance. This study aims to determine the effect of macroeconomic factors on the abnormal return of shipping companies in Indonesia. Data analysis methods used to test hypotheses in research are using Multiple Linear Regression Analysis and Path Analysis. The determination of the sample in this study used a purposive sampling method. The result showed that ROE could not partially be an intervening variable between macroeconomics and abnormal return.